A Comparison of Five Different Treatment Regimens as the First‐Line Treatment of Helicobacter pylori in Turkey. Issue 4 (1st December 2015) - Unler, Gulhan Kanat; Teke Ozgur, Gulsum; Gokturk, Huseyin Savas; Karakoca, Aydın; Erinanc, Ozgur Hilal
Abstract: Background: The H. pylori eradication success is low in countries with high antibiotic resistance to H. pylori . Objective: We retrospectively assessed the eradication rates achieved by five different regimens and aimed to compare the efficiency of bismuth enhanced sequential therapy and other treatments in a gastroenterology outpatient clinic a university‐affiliated hospital. Design: Our study was carried out with a retrospective cohort design. Setting: This study assessed the gastroscopy examinations of patients. Patients: A total of 621 patients were included in the study. There were 122 patients in the quadruple treatment group, 168 patients in the classical sequential treatment group, 130 patients in the bismuth enhanced sequential therapy, 113 patients in the sequential treatment with levofloxacin, and 88 patients in the hybrid treatment. Measurements: Eradication rates of different regimens was analyzed by performing Chi‐square and Tukey's honest significant difference test. Results: Eradication rates by ITT and PP analysis achieved by treatment groups were 74.6 and 75.6% in the quadruple treatment; 70.2 and 70.4% in the sequential treatment with clarithromycin, 88.5 and 90.3% in the bismuth enhanced sequential therapy, 77.9 and 78.5% in the sequential treatment with levofloxacin, and 76.1 and 76.2% in the hybrid treatment. Limitations: The main limitation of our study was its retrospective nature. Different proton pump inhibitors were used in the treatment arms. Conclusions: Bismuth‐enhanced sequential therapy can be recommended to overcome resistance.